Amorphous biogenic silica production and utilization in experimental dental composites: Effect of silica gel formation pH on silica and composite properties - Basaran Elalmis, Yeliz; Yucel, Sevil; Aydin, Ismail (WILEY, 2021)
The purpose of this present study was to synthesize biogenic silica from rice hull ash (RHA) and investigate the effect of silica gel formation pH on the properties of silica powders and light-cured experimental dental composites (EDCs) prepared using biogenic silica powders. Silica extracted from RHA and silica powders with different properties were obtained by the gelation of silicate solutions at pH 4, 7, and 9. Silica samples were characterized using inductively coupled plasma/optical emission spectrometry, X-ray diffraction spectroscopy, Fourier-transform infrared spectroscopy, scanning electron microscopy, laser particle sizer, and N-2 adsorption analysis. Silanated silica powders were mixed with organic matrix (bisphenol A-glycidyl methacrylate 50 wt%-2-hydroxyethyl methacrylate 50 wt%) and EDC obtained were subjected to Vickers hardness, three-point bending, and degree of conversion (DC) tests. EDC paste prepared with the inclusion of silica powder produced from pH 9 gel (9SiO(2)) could not be cured. EDC prepared with silica produced from pH 4 gel (4SiO(2)) had higher flexural strength than composite prepared with silica produced from pH 7 gel (7SiO(2)) at the same wt%. EDCs prepared using 9SiO(2) showed significantly lower DC compared to EDCs prepared with 4SiO(2) and 7SiO(2). These observations reveal that EDC properties are susceptible to silica gel formation pH just as the obtained biogenic silica properties are. Furthermore, this study indicates the importance of optical properties of filler designed for light-cured dental composites. Biogenic silica powders obtained from RHA may be low-cost alternatives to current amorphous silica fillers depending on the production conditions.
Keywords: biogenic silica; dental composite; mechanical properties; rice hull ash silica; RICE HUSK ASH; SURFACE-AREA NANOSILICA; MECHANICAL-PROPERTIES; FILLER CONTENT; PARTICLES; RESINS; NANOPARTICLES; ADSORPTION; BIOMASS; CARBON; Materials Science; Polymer Science